Temperature dependent deformation behavior and stacking fault energy of Fe40Mn40Co10Cr10 alloy. (1st July 2021) - Chandan, A.K.; Tripathy, S.; Sen, B.; Ghosh, M.; Ghosh Chowdhury, S.
Abstract: The variation in stacking fault energy (SFE) with the change in temperature has been evaluated experimentally for Fe40 Mn40 Co10 Cr10 high entropy alloy. The distance between partial dislocations was measured using transmission electron microscopy (TEM) based weak-beam dark field (WBDF) technique. SFE of the system was found to be 37.7 (±7) mJ/m 2 and 19.5 (±5) mJ/m 2 at room temperature (RT) and -100°C, respectively. Owing to the decrease in SFE, a transition in the deformation behavior occurred from limited twin formation and slip dominance at RT to mixed-mode consisting of FCC→HCP transformation and twinning at -100°C. Simultaneous occurrence of twins and deformation-induced martensitic transformation led to superior strength-ductility combination in the specimen deformed at -100°C. SFE of the studied alloy at RT was 42% higher than that of the equiatomic FeMnCoCrNi alloy. This increase in SFE, despite removal of Ni can be understood by considering the effect of the alloy chemistry re-adjustment on Δ G γ → ε . Graphical Abstract: Image, graphical abstract